Louis Wolfson: as palavras de escritura fina - Marini, Caroline Pessalácia (2010)
In this paper, we propose to reflect about the functioning of the delirium in the language, from Wolfson s production, considering two main aspects, his relation with several languages and his refusal of the language taught by his mother. To make our discussion, we will start from the articulation between language and psychoanalysis proposed by Jacques Lacan, begining with the re-reading of Freud and his concepts brought from linguistic area (based on Ferdinand Saussure). Freud and Lacan worry about making a distinction between neurosis and psychosis to define the structural mechanisms of each functioning. Lacan bases on some concepts proposed by Ferdinand Saussure about the language functioning, principally the linguistic sign to explain the inscription way of the subject in the language fields and the features of each structure. Our focus will be destinate to a deepening in the area of the psychosis structuration. In this way, it will be considered: the concepts concerning such strucuture, like Verwerfung of the Father s Name, the peculiar organization of the meanings and the predominance of the metonimic operation in the relation to the methaforic ones. Such concepts are related to the constitution of the delirium and the logics of the functioning. The delirium is presented in the phychoses like a possibility of the reconstruction of the reality and a reorganization of the meaningful chain, wich is marked with a break due to the lack of the father functioning. Maleval, in the book Le logique du délire, deepens in his conception about the delirium both in the psychiatry and psychanalysis; the author bases on the psychanalysis to detach the phases of the elaboration of the delirium, as well asw his way of systematization. To understand the mechanisms that make the chain of the language funcioting of the psychosis, as well as the elaboration and the work of the delirium, we base on the reports by Louis Wolfson ( author of the book Le schizo et les Langues). With this discussion cocnerning Wolfson s piece, we aim to detach the functioning of specific language and also the peculiar relation with the meanings, caused by the lack of the father s function and ther relation of the refusal of mother s wish and the language taught by her. Further more, we search to investigate the systematization of the delirium from the author s reportrs, considering mainly the aspects like the refusal of the language taught by his mother, the relation established by Wolfson With his several other languages chosen to substitute the one that could be his mother language.